Nonlinear influences of stressors on general adjustment: the case of Japanese expatriates and their spouses - Takeuchi, Riki; Lepak, David P; Marinova, Sophia V; Yun, Seokhwa (Journal of International Business Studies, 2007)
Integrating research on parental demands, learning, and expatriate adjustment, we examine potential nonlinear influences of two stressors – parental demands and perceived culture novelty – on general adjustment of expatriates and their spouses. Using a sample of 170 matched pairs of Japanese expatriates and spouses assigned to the US, we found a quadratic effect of parental demands and a cubic effect of cultural novelty on spouse general adjustment but not on expatriate general adjustment. Implications and directions for future research are discussed.